Putative Role of Adipose Tissue in Growth and Metabolism of Colon Cancer Cells - Schwartz, Betty; Yehuda-Shnaidman, Einav (Frontiers in Oncology, 2014)
Newly emerging data highlight obesity as an important risk factor for developing certain types of cancer, including colorectal cancer. Although evidence supports a link between the two, the mechanisms responsible for this relationship have not yet been fully elucidated. Hypertrophied and dysfunctional adipose tissue of the obese state is characterized by low-grade inflammation. Adipokines and cytokines secreted from adipocytes, together with the abundant availability of lipids from adipocytes in the tumor microenvironment, promote adhesion, migration, and invasion of tumor cells and support tumor progression and uncontrolled growth. One of the predisposed targets of the deleterious effects exerted by secretions from adipose tissue in obesity are the activities associated with the cellular mitochondria. Mitochondrial oxidative metabolism plays a key role in meeting cells' energetic demands by oxidative phosphorylation (OxPhos). Here we discuss: (a) the dynamic relationship between glycolysis, the tricarboxylic acid (TCA) cycle, and OxPhos; (b) the evidence for impaired OxPhos (i.e. mitochondrial dysfunction) in colon cancer; (c) the mechanisms by which mitochondrial dysfunction can predispose to cancer. We propose that impaired OxPhos increases susceptibility to colon cancer since OxPhos is sensitive to a large number of factors that are intrinsic to the host (e.g. inflammation). Given that adipocytes are a major source of adipokines and energy for the cancer cell, understanding the mechanisms of metabolic symbiosis between cancer cells and adipocytes should reveal new therapeutic possibilities.